ANALISIS FMEA DEFECT RUN OUT PADA PRODUCT BAN SEPEDA DI PT. H-AI - Kurniawan, Iwan; Ernawati; Giyats Al-Salamah, Nurwahidah (LPPM Sekolah Tinggi Teknologi Cipasung, 2024)
Run Out is a defect where the tire rotation position is out of the center line position. The cause of this defect is the most complicated and difficult to identify, because various sources of problems influence the occurrence of this defect. Anticipating the occurrence of Defect Run Out is carried out through improvement stages based on the six sigma program with a focus on its implementation being carried out continuously throughout 4M+1H. The initial step in the Six Sigma process is Failure Mode Effect Analysis (FMEA) which is a structured procedure to identify and prevent as many failure modes as possible with the methodology used including research and descriptive data collection. Data analysis carried out revealed 76 possible potential failures, based on the highest RPN value, it appeared that there were 26 most dominant causes of failure. The highest values are grouped into 3 categories, this is to simplify the improvement and sampling process. After the analysis and improvement process was carried out, the defect condition decreased slightly, amounting to 47.2% and improvements will continue to be made to achieve the lowest defect value.